Wednesday

April 23, 2014

April 23, 2014

Posted by **Jimmy** on Thursday, April 10, 2008 at 12:55pm.

2(3x - 1) - 3(x - 2) = 4x

- Maths -
**drwls**, Thursday, April 10, 2008 at 12:59pm6x -2 -3x +6 = 4x

3x +4 = 4x

x = 4

- Maths -
**Jimmy**, Thursday, April 10, 2008 at 1:15pmThank you i kept getting the +6 as a negative time for a break i think

- Maths -

**Related Questions**

Algebra 2 - Absolute Value Equations Will someone please check to see if I am ...

math - x^2-3x+2<0 Put in y=x^2-3x+2 in your graphing calculator, and graph is...

Algebra - √(y+4)-4=1 Y = or no solution I keep coming back to no solution ...

Chemistry(Please check answers) - 1) For a reaction delta Go is more negative ...

Alg 1 - What are the approximate solutions of 2x^2 -x + 10 = 0 In working this, ...

algebra - But I am getting more and more confused. -3-3x=-9????? and x/6=-24 but...

microeconomics - Fact 1: "The substitution effect(SE) must ALWAYS be negative (i...

algebra - find the minimum value of f(x,y) equals x minus 4y for the feasible ...

Technology-Labs - I have these labs that I have to complete for my Intro to ...

Algebra - I am so confused with the rules of exponents. I know them, but I have ...